2020
DOI: 10.1093/jpepsy/jsaa024
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Sleep Intervention in Urban Primary Care: Caregiver and Clinician Perspectives

Abstract: Background Despite significant income-related disparities in pediatric sleep, few early childhood sleep interventions have been tailored for or tested with families of lower socio-economic status (SES). This qualitative study assessed caregiver and clinician perspectives to inform adaptation and implementation of evidence-based behavioral sleep interventions in urban primary care with families who are predominantly of lower SES. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…69 Studies using qualitative methods have provided insights into the ways in which different socio-ecological factors may interact to create barriers to healthy sleep for youth and their families of primarily lower-SES and nonwhite backgrounds. 70,71…”
Section: Disparities In Pediatric Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Studies using qualitative methods have provided insights into the ways in which different socio-ecological factors may interact to create barriers to healthy sleep for youth and their families of primarily lower-SES and nonwhite backgrounds. 70,71…”
Section: Disparities In Pediatric Sleepmentioning
confidence: 99%
“…71 Overall, identifying youth, family, and other stakeholder perceptions about sleep health and treatments is critical for developing and implementing acceptable and efficacious methods to address pediatric sleep disparities. 70,71…”
Section: Approaches To Addressing Pediatric Sleep Disparitiesmentioning
confidence: 99%
“…By understanding barriers, the authors were able to pilot a well-received intervention for these patients. A qualitative study ( Williamson et al., 2020 ) of caregivers and clinicians focused on identifying ways to adapt and implement evidence-based interventions for primarily Black-identified toddlers and preschoolers presenting with sleep issues in an urban environment relegated for people experiencing low socioeconomic status. The findings highlight the common and unique concerns of caregivers and clinicians living and working in these environments; thus, emphasizing the value of attaining both perspectives when designing and preparing to implement interventions in settings relegated to have fewer resources.…”
Section: Factors Impacting Implementation Of Interventions To Addressmentioning
confidence: 99%
“…In a study comparing attitudes toward adopting EBPs for autism, providers reported that they thought many EBPs were not a good fit for children treated in community settings (Stahmer & Aarons, 2009). A study evaluating community clinicians' use of a behavioral intervention for toddlers and preschoolers with sleep difficulties found that clinicians were less likely to use the intervention with families that they perceived as experiencing stressors often ascribed to families from lower socioeconomic status, such as inflexible or variable work schedules, close living quarters, and neighborhood safety concerns (Williamson et al, 2020). Similarly, EI providers described families as being either "conducive" or "unconducive" to family-centered practices, with unconducive families most often being those who were poor or minorities.…”
mentioning
confidence: 99%